Peran Pendidikan Multikultural dalam Membangun Masyarakat yang Harmoni di Indonesia - Abd. Amri Siregar (Al-Khair Journal: Management Education, 2024)
Abstract: Multicultural education is still difficult to play a role in building a harmonious society, marked by frequent multicultural conflicts in society. The purpose of this study is to map and analyze the role of multicultural education in building a harmonious society. Using a descriptive qualitative method. The results of the study show that multicultural education has fought a war in building a harmonious society through understanding and appreciating diversity, but there are still often multicultural conflicts in society triggered by differences in religion, belief, belief, ideology, politics, socio-economy, culture, race, ethnicity, customs, gender, resulting in prolonged debates, disputes, fights, and fights in society. Therefore, it can be concluded that multicultural education has played a role in building a harmonious society through understanding and appreciating diversity. Thus, it can be suggested that, to build a harmonious society, increase the role of multicultural education in Indonesia.Keywords: The Role of Multicultural Education, Building a Harmonious Society Abstrak: Pendidikan multicultural masih sulit berperan dalam membangun masyarakat yang harmoni, ditandai masih sering terjadi konflik multikultural dalam masyarakat. Tujuan penelitian ini untuk memetakan dan menganalisis peran pendidikan multikultural dalam membangun masyarakat yang harmoni. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa pendidikan multikultural telah berperan dalam membangun masyarakat yang harmoni melalui pemahaman dan menghargai keberagaman, namun masih sering terjadi konflik multikultural dalam masyarakat yang dipicu oleh perbedaan agama, keyakinan, kepercayaan, ideology, politik, sosial ekonomi, budaya, ras, suku, adat istiadat, dan gender, sehingga mengakibatkan perdebatan yang berkepanjangan, perselisihan, cekcok, dan perkelahian yang tidak kunjung selesai dalam masyarakat. Oleh karena itu dapat disimpulkan bahwa pendidikan multikultural telah berperan dalam membangun masyarakat yang harmoni melalui pemahaman dan menghargai keberagaman. Dengan demikian dapat disarankan, untuk membangun masyarakat yang harmoni, maka tingkatkanlah peran pendidikan multikultural di Indonesia. Kata kunci: Peran Pendidikan Multikultural, Membangun Masyarakat yang Harmoni